2023
DOI: 10.1101/2023.01.09.523147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification, characterisation and recombinant expression of flavonoid 3’,5’-hydroxylases and cytochrome P450 reductases fromVacciniumspecies

Abstract: Flavonoid 3',5'-hydroxylases (F3′5′Hs) play a key role in biosynthesis of blue coloured anthocyanin complexes in plants. Thus these proteins have potential application in the development of a natural blue coloured food dye using microbial cell factories. However, F3′5′Hs are membrane proteins that require a redox partner, NADPH-cytochrome P450 reductase (CPR). The aim of the research was to identify F3′5′H sequences from Vaccinium species plants and express the respective proteins in yeast to test their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…The finding of the whole blueberry genome sequence enables the performance of whole-genome F3′5′H gene analysis [32]. F3′5′H family research showed that F3′5′H members are related to anthocyanin biosynthesis, abiotic stress, and hormone signaling [10,33,34]. Anthocyanin accumulation at different developmental stages of blueberries resulted in color-phenotype differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of the whole blueberry genome sequence enables the performance of whole-genome F3′5′H gene analysis [32]. F3′5′H family research showed that F3′5′H members are related to anthocyanin biosynthesis, abiotic stress, and hormone signaling [10,33,34]. Anthocyanin accumulation at different developmental stages of blueberries resulted in color-phenotype differentiation.…”
Section: Introductionmentioning
confidence: 99%